Communications institutionnelles sur le net et diffusion de bonnes pratiques en matière de développement durable - Annick Schott-Seraudie (Netcom)
Since 2002 French companies (and companies registered in France) have had to account for the social and environmental impacts of their activities by law. “By communicating on its social or environmental responsibility, a company commits itself to act according to what it said” (Laville, 2002). What about the declarations of company managers, included in their sustainable development report? Since communication includes dialogue (Wolton, 2005), our tools will be based on relational analysis developed by the Palo Alto school.